Effect of the Head of Bed Elevation on Back Pain After Elective Coronary Angiography: A Randomized Controlled Trial - TÜREN, SEVDA; YILMAZ, RAHİME ATAKOĞLU; Yeşiltepe, Nezahat; Bektaş, İbrahim (W.B. Saunders, 2022)
Background: Patients are restricted to bed and required to lie flat after coronary angiography (CAG) due to potential risk of vascular complications. This often cause back pain. Aim: We aimed to investigate effect of the head of bed (HOB) elevation on back pain and vascular complications after elective CAG. Methods: Three hundred and seven consecutive patients who underwent elective CAG were randomized into three groups. One control (HOB: 0 degree-flat position) and two experimental (HOB: 15 and 30°) groups were compared. Back pain level was assessed by using visual analogue scale. Results: Mean age was 58.1 ± 10.7 and 59.9% (n = 184) of patients were male. Pain level at the 3rd hour and at the 6th hour was significantly higher in control group compared to experimental groups. In the post-hoc analysis, pain level was significantly higher in HOB 15 compared to 30°. In multivariate analysis, HOB elevation to 30° was the only independent predictor of the pain level at 3rd hour and 6th hour. Only one patient in the HOB 0 degree group had a minor bleeding at the access site. Conclusions: Elevation of the HOB to 30° was associated with decreased back pain level without increased risk of vascular complications. © 2022 Elsevier Inc.
Keywords: Back Pain; Coronary Angiography; Head of Bed Elevation